A subset of metastatic pancreatic ductal adenocarcinomas depends quantitatively on oncogenic Kras/Mek/Erk-induced hyperactive mTOR signalling - Kong, Bo; Wu, Weiwei; Cheng, Tao; Schlitter, Anna Melissa; Qian, Chengjia; Bruns, Philipp; Jian, Ziying; Jäger, Carsten; Regel, Ivonne; Raulefs, Susanne; Behler, Nora; Irmler, Martin; et al. (Gut, 2016)
ONCOGENES; PANCREATIC CANCER; PANCREATIC PATHOLOGY
Published Online First 19 January 201
Gesehen am 29.06.2020
"Epub 2015 Jan 19."